2016
DOI: 10.1186/s13024-016-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid Presenilin-1 increases at asymptomatic stage in genetically determined Alzheimer’s disease

Abstract: Background: Presenilin-1 (PS1), the active component of the intramembrane γ-secretase complex, can be detected as soluble heteromeric aggregates in cerebrospinal fluid (CSF). The aim of this study was to examine the different soluble PS1 complexes in the lumbar CSF (CSF-PS1) of individuals with Alzheimer's disease (AD), particularly in both symptomatic and asymptomatic genetically determined AD, in order to evaluate their potential as early biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…Here, we replicated the occurrence of the ~500 kDa reelin in AD CSF by treating the cells with amyloidogenic Aβ42. Interestingly, complexes of several CSF proteins, such as presenilins [ 57 , 58 ], cholinesterase [ 59 ], and apoE [ 60 , 61 ], formed under amyloidogenic conditions appear to be particularly stable. Reelin interacts with Aβ both in vitro [ 62 ] and in vivo [ 19 ], as it is recruited into amyloid fibrils; thus, we hypothesized that Aβ played a direct role in the formation of the 500 kDa reelin species detected in AD CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we replicated the occurrence of the ~500 kDa reelin in AD CSF by treating the cells with amyloidogenic Aβ42. Interestingly, complexes of several CSF proteins, such as presenilins [ 57 , 58 ], cholinesterase [ 59 ], and apoE [ 60 , 61 ], formed under amyloidogenic conditions appear to be particularly stable. Reelin interacts with Aβ both in vitro [ 62 ] and in vivo [ 19 ], as it is recruited into amyloid fibrils; thus, we hypothesized that Aβ played a direct role in the formation of the 500 kDa reelin species detected in AD CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Among the substrates of these proteases are, according to MEROPS, amyloid beta A4 protein in CSF, E‐cadherin in serum, and albumin in saliva (Table S1, Supporting Information). The presence of presenilin‐1 in CSF was already associated to AD . Presenilin‐1 appears to be also related to plasma and serum peptidomes; however, as far as we know, no previous assessment of its levels on these fluids was reported.…”
Section: Comparative Analysis Of Proteases Distribution Among Distincmentioning
confidence: 94%
“…In contrast with BACE1, changes in APP, PSEN1, and PSEN2 protein levels have been considered unsuitable biomarkers in human fluids. Only two studies have shown that the levels of soluble PSEN1 complexes are increased in ventricular postmortem CSF from AD patients compared to control individuals [143] as well as in lumbar CSF samples obtained from genetically determined AD patients [144]. Regarding PSEN2, a transcript named PSV2 encoding a truncated form of PSEN2 is upregulated in AD postmortem brains [145].…”
Section: Role Of Genes For β-Secretases (Bace1 and Bace2mentioning
confidence: 99%